A Study on Risk Assessment Myopic Score at Tertiary Eye Care Center - Niravkumar Mehta; Payal Patel; Paras Desai (Delhi Journal of Ophthalmology, 2025)
Aim: This study aimed to assess the risk assessment myopic score (RAMS). • The objective of this study is to assess the RAMS, • To assess the risk of parental myopia in myopia progression, • To assess the relationship between changes in SE and axial length (AXL) and the risk of myopia progression. Materials and Methods: The prospective, cross-sectional study was conducted at a tertiary eye care center, and 113 patients aged 6–16 years were seen in the outpatient department of Rotary Eye Hospital. This study was conducted with myopic patients (short-sightedness). This study created a scoring system to evaluate effective strategies for managing myopia and introduced a “RAMS.” This score incorporates various established risk factors, such as parental myopia, environmental factors, and changes in refractive error spherical equivalent (SE) and AXL, to identify individuals at risk for myopia progression. To determine the AXL, a noncontact biometer will be used. The RAMS was identified using the risk factors score, which was analyzed and calculated using IBM SPSS Statistics Software. Results: A total of 113 patients were included. Among these, 56 (49.55%) were female and 57 (50.45%) were male. Age ranges from 6 to 16 years. The mean ± standard deviation (SD) age of onset and age at presentation of 113 myopic individuals were 9.56 ± 3.04 and 11.7 ± 3.01, respectively. The mean changes in spherical equivalent refraction were −3.44 ± 2.04 D and -3.34 ± 1.90 D for the right and left eyes, respectively. The average number of hours spent on near-work activities was 1.97 ± 0.67 h/day, and on outdoor activities, it was 1.65 ± 0.63 h/day. The number of myopic parents (0, 1, and 2) was 57, 35, and 21, respectively. The mean number of myopic parents was 1.68 ± 0.77. The mean of near-phoria was 1.82 ± 0.38 PD, respectively. The total mean ± SD of the score of the risk factor was 22.68 ± 4.73. Out of 113 patients, 29 were at “low risk” of their myopia progressing, 45 were at “moderate risk,” and 39 were at “high-risk” conditions. The mean AXL was 24.85 ± 1.14 mm and 24.80 ± 1.15 mm for the right and left eyes, respectively. The mean Average K values for the right and left eyes were 44.20 ± 1.41 mm and 44.25 ± 1.46 mm, respectively. The research results show a significant and strong correlation between changes in AXL and SE, yet only for the right and left eyes (r = 0.93 and 0.94, respectively). The myopia progression risk grade mean was 1.91 ± 0.77. The mean of the genetic risk was 2.31 ± 0.77, the mean of the environmental risk was 1.84 ± 0.59, the mean of the individual risk was 1.66 ± 0.78, and the mean of the overall risk was 1.91 ± 0.77. RAMS risk score grade (low, medium, high) and risk grade (low, medium, high) for identifying the presence of the risk of myopia progression in patients. The results indicated perfect agreement between the raters, with a Kappa value of k = 0.820, SE = 0.057, T = 10.857, P < 0.05. Conclusion: We conclude that the RAMS is a tool or system used to assess the risk score of a myopic patient. We conclude that the higher the risk factors present in a myopic patient, the higher the risk score. RAMS can assess the risk score based on risk factors such as age of presentation, age of onset, wearing myopic correction or not, number of myopic parents, time spent at work, and time spent outdoors. All myopic patients should be assessed with the help of the RAMS tool to identify their myopic risk score.